Resistências surdas : quando as narrativas dos tradutores e intérpretes de Libras e Português nos contam as histórias - Silva, Josué Rego da (2018)
This study brings to discussion the origin, composition and institutionalization of the Brazilian Sign Language and Portuguese Translator and Interpreter in the mandatory of inclusion. It seeks to comprehend how deaf resistances modes arise from the experiences and practices of this professional pondering about his placement inside inclusive schools. The authors that compose the theoretical framework are Foucault (1971, 1995, 2006, 2013, and 2016), by considering the concepts of power relations and resistance; Veiga-Neto (2011), Lopes and Fabris (2013), when it comes to translators and interpreters institutionalization as a possible biopolitical strategy to manage the deaf presence risk in social environments, especially inside the schools. The Biopolitics as a way to exercise power beyond the disciplinary authority emerges with the concept of population from the XVIII century on, and creates, through practices of government and subjectivation, the different forms of resistance towards the individuals’ action management. We analyzed narratives collected from experienced people related to the Libras, Portuguese translation, and interpretation area between 29 and 55 years old from different states of Brazil. The hypothesis consists on the fact that the Brazilian Sign Language and Portuguese Translator and Interpreter came up as a risk management device of the deaf individuals inside the schools, based on the inclusion intelligibility blueprint that assumes the role to govern the behavior of the subjects labelled inside this rationality target audience. I believe that in different moments along their own history, these people ressonated in their practices, which I understand as deaf resistances, as ways to struggle against the power relations, control and body regulations in different spaces. When analyzing the Brazilian Sign Language and Portuguese Translator and Interpreter in the inclusion system through a Foucault’s perspective, many possibilities are taken without previously assuming any statement about this professional.